NuRD Blocks Reprogramming of Mouse Somatic Cells into Pluripotent Stem Cells - Luo, Min; Ling, Te; Xie, Wenbing; Sun, He; Zhou, Yonggang; Zhu, Qiaoyun; Shen, Meili; Zong, Le; Lyu, Guoliang; Zhao, Yun; Ye, Tao; Gu, Jun; et al. (Stem cells (Dayton, Ohio), 2013)
Reprogramming of somatic cells into induced pluripotent stem cells (iPSCs) by overexpression of a defined set of transcription factors requires epigenetic changes in pluripotency genes. Nuclear reprogramming is an inefficient process and the molecular mechanisms that reset the epigenetic state during iPSC generation are largely unknown. Here, we show that downregulation of the nucleosome remodeling and deacetylation (NuRD) complex is required for efficient reprogramming. Overexpression of Mbd3, a subunit of NuRD, inhibits induction of iPSCs by establishing heterochromatic features and silencing embryonic stem cell‐specific marker genes, including Oct4 and Nanog. Depletion of Mbd3, on the other hand, improves reprogramming efficiency and facilitates the formation of pluripotent stem cells that are capable of generating viable chimeric mice, even in the absence of c‐Myc or Sox2. The results establish Mbd3/NuRD as an important epigenetic regulator that restricts the expression of key pluripotency genes, suggesting that drug‐induced downregulation of Mbd3/NuRD may be a powerful means to improve the efficiency and fidelity of reprogramming. STEM Cells2013;31:1278–1286